2011 IEEE International Test Conference 2011
DOI: 10.1109/test.2011.6139189
|View full text |Cite
|
Sign up to set email alerts
|

Power, programmability, and granularity: The challenges of ExaScale computing

Abstract: Reaching an ExaScale computer by the end of the decade, and enabling the continued performance scaling of smaller systems requires significant research breakthroughs in three key areas: power efficiency, programmability, and execution granularity. To build an ExaScale machine in a power budget of 20 MW requires a 200-fold improvement in energy per instruction: from 2 nJ to 10 pJ. Only 4x is expected from improved technology. The remaining 50x must come from improvements in architecture and circuits. To program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…For a vEB tree with the same height, the required block transfers is only two. As shown in Figure 2b, locating the key in leaf-node 12 requires only a transfer of nodes (1, 2, 3), followed by a transfer of nodes (10,11,12). Generally, the data transfer (or I/O) complexity of searching for a key in a tree of size N is now reduced to log 2 N log 2 B = log B N , simply by using an efficient tree layout so that nearby nodes are located in adjacent memory locations.…”
Section: Design Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…For a vEB tree with the same height, the required block transfers is only two. As shown in Figure 2b, locating the key in leaf-node 12 requires only a transfer of nodes (1, 2, 3), followed by a transfer of nodes (10,11,12). Generally, the data transfer (or I/O) complexity of searching for a key in a tree of size N is now reduced to log 2 N log 2 B = log B N , simply by using an efficient tree layout so that nearby nodes are located in adjacent memory locations.…”
Section: Design Overviewmentioning
confidence: 99%
“…Recent researches have suggested that the energy consumption of future computing systems will be dominated by the cost of data movement [12,34,35]. It is predicted that for 10nm technology chips, the energy required between accessing data in nearby on-chip memory and accessing data across the chip, will differ as much as 75× (2pJ versus 150pJ), whereas the energy required between accessing on-chip data and accessing off-chip data will only differ 2× (150pJ versus 300pJ) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of power consumption has become an important problem in not only super computers but also electronic devices [1], [2]. For example, the concept, dark silicon, comes from the gap between Moore's Law [3] and Dennard scaling [4]; the shortage of LSI power disables a larger fraction of circuits whenever process rule advances.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution trend of computing architectures shows an increasing gap between computational performance and bandwidth to off-chip memory [8]; it is already apparent that while GPUs have a theoretical compute performance ten times higher than CPUs, the bandwidth to off-chip DRAM is only 3-5 times faster. Also, with an increasing number of cores on a single chip the amount of on-chip memory per core decreases.…”
Section: Introductionmentioning
confidence: 99%